The time spent on board games pays off: links between board game playing and competency motivation - Dukán, András Ferenc; Fried, Katalin; Szabó, Csaba (Teaching Mathematics and Computer Science, 2021)
The impact playing has on the development of thinking is an important topic of psychology of learning, brain research and mathematics didactics. Our research is also connected to the aforementioned topic. We investigated the effects of playing board games on competence motivation and the development of mathematical competencies. In this paper, we present the results of an experiment carried out in a secondary school class. The experimental group spent one of three weekly mathematics lessons playing board games. Apart from the several advantages of playing games in general, we can conclude that, based on the results of the national competence measurement, the mathematical competence of the students developed properly. The readiness and the progress of the pupils were compared on the basis of input and output tests and an initial knowledge measurement and, at the same time, we compared their level of mathematical competence with the results of the national competence measurement. Subject Classification: 97C70, 97D40